2002
DOI: 10.1046/j.1523-1755.2002.00459.x
|View full text |Cite
|
Sign up to set email alerts
|

Bile acid binding to sevelamer HCl

Abstract: The favorable bile acid binding characteristics of sevelamer provide a compelling explanation for its ability to lower LDL cholesterol in hemodialysis patients and in healthy volunteers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
74
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 21 publications
1
74
0
1
Order By: Relevance
“…However, it is possible that the concomitant administration of phosphate binders with oral VDRAs may result in drug-drug interactions, thereby reducing the therapeutic activity of these oral VDRAs. Preclinical studies have shown that sevelamer (SEV) hydrochloride (Renagel®) has a high affinity for bile acids, which may impair the absorption of fat-soluble vitamins, including vitamin D [6]. Furthermore, a pharmacokinetic study in healthy human subjects found that SEV binds to exogenous oral calcitriol, reducing its bioavailability [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is possible that the concomitant administration of phosphate binders with oral VDRAs may result in drug-drug interactions, thereby reducing the therapeutic activity of these oral VDRAs. Preclinical studies have shown that sevelamer (SEV) hydrochloride (Renagel®) has a high affinity for bile acids, which may impair the absorption of fat-soluble vitamins, including vitamin D [6]. Furthermore, a pharmacokinetic study in healthy human subjects found that SEV binds to exogenous oral calcitriol, reducing its bioavailability [7].…”
Section: Introductionmentioning
confidence: 99%
“…Our meta-analysis indicated that sevelamer was significantly more effective than CBPBs in lowering serum TC and LDL. This is apparently due to the binding of sevelamer to bile acids in the intestine, similar to the effect of bile acid sequestrants such as cholestyramine, colestipol, and colesevelam [36]. The resulting loss of bile acids from the enterohepatic circulation and increase in bile acid excretion lead to depletion of hepatic cholesterol and an increase in LDL cholesterol clearance from circulation [36] .…”
Section: Discussionmentioning
confidence: 99%
“…This is apparently due to the binding of sevelamer to bile acids in the intestine, similar to the effect of bile acid sequestrants such as cholestyramine, colestipol, and colesevelam [36]. The resulting loss of bile acids from the enterohepatic circulation and increase in bile acid excretion lead to depletion of hepatic cholesterol and an increase in LDL cholesterol clearance from circulation [36] . It has been suggested that lipid disorders may be related to CAC and atherosclerosis in dialysis patients [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Sevelamer hydrochloride also exhibits bile acid-binding propertiesin vitro [4], which result clinically in LDL cholesterol lowering [5]. Sevelamer hydrochloride has also been shown to bind other organic anions including indoxyl sulfate [6] and uric acid [7].…”
Section: Discussionmentioning
confidence: 99%
“…This effective calcium-free phosphate binder has been used for the treatment of hyperphosphatemia in patients with chronic kidney failure [3]. Sevelamer hydrochloride has also been shown to bind other compounds in the intestinal tract including bile acids [4], which results in the lowering of LDL cholesterol [5], as well as other organic anions such as the uremic toxin indoxyl sulfate [6] and uric acid [7]. When administered concomitantly, sevelamer hydrochloride can also reduce the oral bioavailability of drugs such as ciprofloxacin and thyroxine [8, 9].…”
Section: Introductionmentioning
confidence: 99%